Effects of multi-time scales climate changes on tobaccoplanting counties in Chenzhou city of Hunan Province - Pan, Daiwei; Zhong, Quan; Liao, Yahua; He, Bin; Li, Wujin; Jian, Hong; He, Zhihong; Cao, Zhihui; Xiao, Yansong (Bangladesh Journal of Botany, 2021)
To provide scientific instruction in predicting the climate changes and adopting the suitable measures for field cultivation and management of tobacco, the changes of main climatic parameters on multi-time scales in the six tobacco-planting counties of Chenzhou city in China were studied. Sunshine hours (S) in the six counties had significant positive linear correlation with year (from 1980 to 2020) and precipitation (P) changed irregularly on the scales of year, field-growth period, and rooting and flourishing stages, and they changed significantly in maturing stage. Sunshine hours (S) in the six counties had significant positive linear correlation with year on the scale of rooting stage, changed irregular with year on the scale of year, and showed different change tendencies in different counties in flourishing and maturing stages. On the scale of field-growth period, the daily cumulative temperature (T) was lower than the optimal value in rooting and flourishing stages, but higher than the optimal value in maturing stage. Bangladesh J. Bot. 50(3): 977-985, 2021 (September) Special